O caráter multidimensional da exploração da mão de obra de crianças e adolescentes: uma avaliação do Programa de Erradicação do Trabalho Infantil no Município de Canindé – Ceará - Castro, Vânia Maria Vasconcelos de (2014)
The exploitation of children and adolescents through work is a multidimensional phenomenon. Brand of modern times - the most distant and different territories of the planet - has, however, an uninterrupted historical ballast, in spite of the legal and political background, his fighting coming increasingly integrating agendas of governments. This research was conducted in the town of Caninde, aimed at building an evaluation of a program - Peti - which is part of the child care policy and adolescents, and which states the purpose of eradicating the exploitation of the labor of children and adolescents under 16 years. As the title suggests, this study identified as the exploitation of children and adolescents, is home to a dimension of diversity. In the case of the municipality under study a pilgrimage center focused on faith in the Patron Saint - Saint Francis of Caninde de Chagas - was unveiled at the role of the Catholic Church in the dynamics of maintaining this form of exploitation of children and adolescents. I identified consortia trade and faith that are established in the various expressions of secular and religious powers. The study spells out the reasons, despite the existence of Peti this municipality, children and adolescents, specifically, aged 10-15 years remain in plain sight, performing work activities to support themselves and their families, while the structures that hold, use and enjoy this form of exploitation of this population segment. In an attempt to explain what is unknown about the essence of this phenomenon of exploitation of the labor of children and adolescents in Caninde, some questions erupt: it would be a failure or inefficiency of Living Services and Links of Strengthening available by reference equipment assistance social that interfere in child and adolescent conditions of stay that holding situation? It would be the capital of the offer, embodied in social structures that sustain and utilize the exploitation of children and adolescents through work, more interesting than the offer submitted by social welfare policy, via Peti? Or both? These are issues that emerge and are set up for your needs answers, the embodiment of this study: a qualitative research with an ethnographic approach. In the construction of elements of analysis for the proposed research, the analysis of the speeches were done through in-depth interviews with public officials, participant observation, photographic records and the production of a video with testimonies of families affected by the market of faith, held on 24th September to 4 October 2013.